To Peel or Not to Peel: Pars Plana Vitrectomy with Macular Membrane Peel in Eyes with Abnormalities of Vitreomacular Interface and Coexisting Dry Age-Related Macular Degeneration - Furashova O (Dove Medical Press, 2020)
Olga Furashova, Katrin Engelmann Department of Ophthalmology, Klinikum Chemnitz gGmbH, Chemnitz, GermanyCorrespondence: Olga FurashovaDepartment of Ophthalmology, Klinikum Chemnitz gGmbH, Flemmingstrasse 2, Chemnitz 09116, GermanyTel +49 371 333 33230Fax +49 371 333 33223Email fur.olga@gmail.comPurpose: To evaluate the outcome of macular surgery with ILM- and epiretinal membrane peel associated with significant dry age-related macular degeneration (AMD) as defined by the Age-Related Eye Disease Study (AREDS).Patients and Methods: Institutional. Retrospective case-control study. A total of 42 pseudophacic eyes of 39 patients (7 with full thickness macular hole and 35 with epiretinal membrane) with coexisting dry AMD underwent pars plana vitrectomy (PPV) with internal limiting membrane (ILM) and epiretinal membrane peel. Preoperative and postoperative data including best corrected visual acuity (BCVA), AMD grade according to AREDS, central retinal thickness (CRT), development of choroidal neovascularization (CNV), and central retinal atrophy have been evaluated. Twenty-eight fellow eyes with dry AMD of the included 39 patients served as a control group.Results: A significant improvement in the visual acuity could be observed after surgery (initial BCVA 0.47± 0.31 logarithm of the minimal angle of resolution (logMAR) vs 0.33± 0.29logMAR 9 months postoperatively; p=0.006). CRT decreased significantly after surgery (p< 0.001). In the surgery group, there were 4 eyes (9.5%) with CNV and 1 eye (2.5%) with new central retinal atrophy development after surgery. All these eyes had preoperative AREDS 3 (4 eyes) or AREDS 4 (1 eye) AMD category. In the control group, there was 1 eye (4%) with CNV and 4 eyes (14%) with new central retinal atrophy development during the follow-up of 9 months. These eyes had initially AREDS 2 (1 eye), AREDS 3 (3 eyes) or AREDS 4 (1 eye) AMD category.Conclusion: Eyes with dry AMD of AREDS 3 and AREDS 4 with coexisting VMI abnormalities improve significantly after PPV with membrane peel. While there is a higher risk of CNV development after surgery (9.5%) in these eyes, the vitrectomy does not seem to accelerate central retinal atrophy progression compared to the fellow eyes course.Keywords: macular membrane peel, choroidal neovascularization, pars plana vitrectomy, age-related macular degeneration, ILM, epiretinal membrane peeling